PENERAPAN TEKNOLOGI DAN PENGARUHNYA TERHADAP REKRUTMEN PADA LEMBAGA PERBANKAN ISLAM - NILA MARDIAH (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. A technological development affects all aspect human life. This also happens in the banking world. Technology provides many benefits for banking, but on the other hand the development technology causes work lost in certain positions that affect the recruitment of human resources. This paper describes how banks apply technology in the era digitizing and how it effect the recruitment of human resources.